Dissecting the cryoprotection mechanisms for dehydrins - Cuevas-Velazquez, Cesar L.; Rendón-Luna, David F.; Covarrubias, Alejandra A. (Frontiers in Plant Science, 2014)
One of the common responses of plants to water deficit is the accumulation of the so-called Late Embryogenesis Abundant (LEA) proteins. In vitro studies suggest that these proteins can protect other macromolecules and cellular structural components from the impairments caused by water limitation. Their binding to phospholipids, nucleic acids and/or to divalent cations has suggested multi-functionality. Genetic analyses indicate that these proteins are required for an optimal adjustment of plants to this insult. This diverse information has conducted to propose different models for LEA proteins action mechanisms. Many of these properties are shared by group 2 LEA proteins or dehydrins (DHN), one of the LEA protein families for which large amount of data is available. This manuscript focuses on the different mechanisms proposed for this LEA protein group by analyzing published data derived from in vitro cryoprotection assays. We compared the molar ratio of protectant:enzyme needed to preserve 50% of the initial activity per enzyme monomer to assess different mechanisms of action. Our results add evidence for protein-protein interaction as a protection mechanism but also indicate that some DHNs might protect by different means.